Assessing the Acceptability of Quipper as Learning Management System Among Pupils, Parents and Teachers - San Juan, Ma. Grace V; Astillero, Jeffrey A. (Edu Berkah Khatulistiwa, 2025)
This study assesses the acceptability of Quipper as a Learning Management System (LMS) among pupils, parents and teachers at Holy Trinity Academy of Calamba. As a digital learning tool, integration to education and understanding user perspective is vital for effective implementation and sustained use. The primary objective of this research is to determine how each stakeholder group perceives Quipper in terms of visual appeal, usefulness, user-friendly features, content and accessibility in teaching and learning. A quantitative research design was conducted through a survey questionnaire. Respondents included the primary level pupils, their parents and elementary level teachers at Holy Trinity Academy of Calamba. The study gathered data on the perceived user acceptance based on the file variables mentioned above. Findings indicate that Quipper is highly acceptable across all stakeholder groups. Pupils expressed interest in its interactive and innovative features; parents acknowledged its convenience in tracking their children's academic performance; and teachers appreciated its content and usefulness in lesson delivery and monitoring student performance through various online assessments. Despite the positive responses, challenges such as inconsistent internet access and the need for further digital literacy support were identified. The study concludes that Quipper is an effective and acceptable LMS for the primary level pupils of Holy Trinity Academy of Calamba. The researcher also provided a policy recommendation for the school administration to support and address user concerns.